1975
DOI: 10.1002/jez.1401910204
|View full text |Cite
|
Sign up to set email alerts
|

Gas transport and blood acid‐base balance in diving sea snakes

Abstract: The values of hemoglobin concentration, Hb-O2 affinity and buffering capacity of the blood of six sea snake species considerably overlap values from terrestrial squamates. Decreased blood pH had little effect on the P50 but increased the n-value of Hb-O2 equilibrium curves. The O2 saturation of blood in the dorsal aorta varied between about 30 and 70% during voluntary diving in Acalyptophis peronii and Lapemis hardwickii. Voluntary dives ended when the lung PP02 was about 50 mm Hg and the arterial PO2 about 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 35 publications
2
24
1
Order By: Relevance
“…Graham (1974) has shown that such snakes can get O2 cutaneously during a dive. Seymour and Webster (1975) found no relationship between submergence and heart rate in bea snakcb…”
Section: Vncauwujcs ±Y/oj*mentioning
confidence: 81%
“…Graham (1974) has shown that such snakes can get O2 cutaneously during a dive. Seymour and Webster (1975) found no relationship between submergence and heart rate in bea snakcb…”
Section: Vncauwujcs ±Y/oj*mentioning
confidence: 81%
“…Therefore, a low O2 content in the inspired air does not impose an immediate threat. Seymour and Webster (1975) found that lung and aortic O2 contents converged until just before voluntary emergence in sea snakes, when the lung PO2 was about 50 torr and the blood PO2 was 34 torr. Thus, only about half of the available O2 had been used; the arterial blood was still 44% saturated.…”
Section: Respiratory System and Metabolismmentioning
confidence: 97%
“…Hov/eve*"; Seymour and Webster (1975) found the buffering capacity of sea snake blood to be similar to that of land snakes. Buffering capacity of aquatic turtles is generally higher than in terrestrial tur tles (Robin et al, 1964;Lenfant et al, 1970a).…”
Section: Respiratory System and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations